The language of power in the simile "like a caged bird": a critical discourse analysis of the Assyrian royal lion hunt and Sennacherib's military campaign against Hezekiah of Judah - Lee, Woo Min (Pickwick Publications, 2025)
"This book presents a sociolinguistic study of the Assyrian royal lion hunt and military inscriptions and reliefs, focusing on Sennacherib's campaign against Hezekiah of Jerusalem in 701 BCE. Through a comparative analysis of the lion hunt imagery and Assyrian military tactics, it examines the goals, outcomes, and conflicting ideologies surrounding the campaign as depicted in both Assyrian sources and biblical texts. While much scholarly attention has centered on the biblical narrative, relatively little has been said about the role of Assyrian lion hunt motifs and their relationship to military rhetoric--particularly in the use of the simile "shut up/enclosed like a caged bird" (kīma iṣṣur quppi esirsu). This academic imbalance has led to a limited, and potentially biased, understanding of the campaign. By drawing on a broader spectrum of Assyrian cultural expressions--including royal hunting practices and military records--this book opens the door to a more comprehensive and nuanced discussion of Sennacherib's campaign against Judah." --Publisher